Comparison of Three Solid Phase Materials for the Extraction of Carboxylic Acids from River Water Followed by 2D GC × GC-TOFMS Determination - Bosire, G. O.; Ngila, J. C.; Parshotam, H. (Hindawi Publishing Corporation, 2016)
The extraction and determination of aliphatic and aromatic carboxylic acids as well as their influence on the aromaticity and molecularity relationship of natural organic matter (NOM) in water are reported in this study.Three solid phase extraction (SPE) sorbents were used and their extraction efficiencies evaluated after chromatographic determinations (using gas chromatography with a time of flight mass spectrometer (GC × GC-TOFMS) and liquid chromatography with organic carbon detector (LC-OCD)). More than 42 carboxylic acids were identified in raw water fromthe Vaal River, which feeds the Lethabo Power Generation Station, South Africa, with cooling water. The aromatic carboxylic acid efficiency (28%) was achieved by using Strata™ X SPE while the highest aliphatic carboxylic acid efficiency (92.08%) was achieved by silica SPE.The hydrophobic nature of NOMin water depends on the nature of organic compounds in water, whether aromatic or aliphatic. The LC-OCD was used to assess the hydrophobicity levels of NOM as a function of these carboxylic acids in cooling water. The LC-OCD results showed that the aromatic nature of NOM in SPE filtered water followed the order Silica>Strata X>C-18. From the results, the hydrophobicity degree of the samples depended on the type and number of carboxylic acids that were removed by the SPE cartridges.